2019
DOI: 10.3390/s19214779
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Unmanned Aerial Vehicles—A Multilayer Low-Altitude Airspace Model for Distributed UAV Traffic Management

Abstract: The rapid adoption of Internet of Things (IoT) has encouraged the integration of new connected devices such as Unmanned Aerial Vehicles (UAVs) to the ubiquitous network. UAVs promise a pragmatic solution to the limitations of existing terrestrial IoT infrastructure as well as bring new means of delivering IoT services through a wide range of applications. Owning to their potential, UAVs are expected to soon dominate the low-altitude airspace over populated cities. This introduces new research challenges such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…UAVs offer a pragmatic solution to overcome possible connectivity limitations caused by solely relying on fixed terrestrial IoT infrastructure as well as bring new means of delivering value-added services through a wide range of IoTenabled applications. Figure 4 (right-hand side) as adopted from [5], uses the International Organisation for Standardisation (ISO) and the International Electrotechnical Commission's (IEC) generic architecture of Internet of Things first proposed in ISO/IEC 30141 [19] to illustrate some of the application scenarios, of UAVs within IoT, that will be later explored in detail.…”
Section: A the Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…UAVs offer a pragmatic solution to overcome possible connectivity limitations caused by solely relying on fixed terrestrial IoT infrastructure as well as bring new means of delivering value-added services through a wide range of IoTenabled applications. Figure 4 (right-hand side) as adopted from [5], uses the International Organisation for Standardisation (ISO) and the International Electrotechnical Commission's (IEC) generic architecture of Internet of Things first proposed in ISO/IEC 30141 [19] to illustrate some of the application scenarios, of UAVs within IoT, that will be later explored in detail.…”
Section: A the Prospectsmentioning
confidence: 99%
“…The economic impacts of IoT are therefore beyond doubt, nevertheless, apart from the buzz-term and the idea of interconnected things, IoT is a complex technological paradigm [5]. IoT can be seen as a system of systems as it is not a single technology, but rather an composition of various technologies working together in tandem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best way to prevent this situation is to separate aircraft into different layers in accordance with their current heading, creating a more homogeneous traffic situation in each layer. Similar concepts were employed in [29][30][31][32]; results showed that a vertical segmentation of airspace, by separating traffic with different travel directions into different flight levels, resulted in a lower rate of conflicts, and thus enabled higher capacity. Two factors contributed to this reduction in the conflict rate.…”
Section: Heading-altitude Rulesmentioning
confidence: 99%
“…Unmanned Aerial Vehicle-aided wireless sensor networks (UAV-aided WSN) have gained more and more interest due to their many applications in monitoring, surveillance, and exploring in healthcare, agriculture, industry, and military [1][2][3][4][5]. Among UAVs' applications, one of the key functions is the data collection [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%